2020
DOI: 10.3389/fvets.2020.00297
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Individual Values to Impact Prudent Antimicrobial Prescribing in Animal Agriculture

Abstract: Antimicrobial resistance is a growing public health threat driven by antimicrobial use-both judicious and injudicious-in people and animals. In animal agriculture, antimicrobials are used to treat, control, and prevent disease in herds of animals. While such use generally occurs under the broad supervision of a veterinarian, individual animals are often treated by farm owners or managers. The decision to administer antimicrobials is therefore influenced not only by the clinical situation but also by the motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 73 publications
(102 reference statements)
0
35
0
Order By: Relevance
“…What evidence does exist about vets’ prescribing is, therefore, more tentative than the evidence for doctors’ prescribing, and it is important to continue building this evidence base to strengthen knowledge of non-clinical influences on vets’ prescribing. Furthermore, there are increasing calls for this work to be informed by the social sciences [ 14 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What evidence does exist about vets’ prescribing is, therefore, more tentative than the evidence for doctors’ prescribing, and it is important to continue building this evidence base to strengthen knowledge of non-clinical influences on vets’ prescribing. Furthermore, there are increasing calls for this work to be informed by the social sciences [ 14 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this similarity in these challenges, insights from environmental psychology related to environmental behaviors and values have been drawn upon in developing this study. Furthermore, since this study was conducted, others have also highlighted the potential role of values in influencing vets’ and doctors’ antimicrobial prescribing and stewardship behaviors [ 40 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…The farmers tended to interpret the sector wide targets in an individualistic manner and placed value on their situational knowledge when treating animals with antibiotics. People prefer communication that is tailor-made to them and their values ( 58 ). Thus, veterinarians could share knowledge and understanding about responsible antibiotic use with farmers based on their values (e.g., animal welfare, reputation) through personal stories.…”
Section: Discussionmentioning
confidence: 99%
“…Within this category, typical extension instruments such as articles in agricultural magazines, demonstration farms, leaflets, study days, digital apps, and others are found. This is arguably one of the most used and investigated routes, mainly in the field of social veterinary epidemiology, which is the study of human behavior that affects the causes, spread, prevention and control of animal diseases and health problems (79), and related disciplines (80)(81)(82).…”
Section: Taxonomy Of Amr Interventions: Five Routes To Behavioral Changementioning
confidence: 99%